Gerakan Tarekat dan Pertumbuhan Budaya Berfilosofi di Lombok - Abdul Quddus; Lalu Muhammad Ariadi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2015)
In Indonesia, Sufism has become a focal part of Islam's development from the 13th to the 18th century. Once Islam was widely spread out of Indonesia in the 13th century, Sufism's teaching had metamorphosed into a religious movement known as Sufi order. Through tarekat movement, Islam in Indonesia has grown not only as a religion but also as a fundamental part of cultural entities in the country. Among these cultures is the Culture of Philosophy in Lombok. This article attempts to scrutinize the development of Tarekat Movement and the Culture of Philosophy in Lombok. These two aspects are analyzed through an anthropological study. The study finds that Tarekat Movement has played a significant role in the growth of the Culture of Philosophy in Lombok. Through the Culture of Philosophy, the Muslim people in Lombok learn and understand Islam as a set of logical facts that teaches its adherents about the Divine Reality and wisdom of life. This culture has been transmitted from generation to generation through oral and written transmissions, in which the written way is found within classical manuscripts. Through these media, the doctrines of Sufism have been taught as a means of cherishing the relation amongst God, Man, and Nature.